(untitled) (Communications in Computational Physics, 2018)
A compressible and multiphase flows solver has been developed for the study of liquid/gas flows involving shock waves and strong expansion waves leading to cavitation. This solver has a structure similar to those of the one-fluid Euler solvers, differing from them by the presence of a void ratio transport-equation. The model and the system of equations to be simulated are presented. Results are displayed for shock and expansion tube problems, shock-bubble interaction and underwater explosion. Close agreement with reference solutions, obtained from explicit finite volume approaches, is demonstrated. Different numerical methods are additionally displayed to provide comparable and improved computational efficiency to the model and the system of equations. The overall procedure is therefore very well suited for use in general two-phase fluid flow simulations.